Implementasi Sistem Pakar Diagnosis Penyakit Gigi dan Mulut Berbasis Web dengan Metode Hybrid Chaining - Reizandi, Dwisatya; Witanti, Arita (JATISI, 2025)
Dental and oral health issues remain prevalent in Indonesia, hindered by limited access to healthcare services and low public awareness. This study aims to develop a web-based expert system for diagnosing dental and oral diseases using a hybrid chaining method that combines the strengths of forward and backward chaining. The system is built using PHP and MySQL, utilizing symptom data and medical records from a dental clinic in Yogyakarta as its knowledge base. Users can perform self-diagnosis by selecting symptoms, and the system provides probable diagnoses along with initial treatment suggestions. The inference process starts with forward chaining to filter potential diseases, followed by backward chaining to verify and calculate the match percentage. Testing on 50 patient records showed an accuracy of 75%. While the accuracy is moderate, the system demonstrates potential as a preliminary diagnostic tool. Further development is recommended, including expanding the rule base, incorporating symptom weighting, and increasing the range of detectable diseases. This system is expected to improve early diagnosis access and public awareness of oral health through digital solutions.